Aprendizagem ativa aplicada à problemática de resíduos sólidos na cidade de Simão Dias - SE - Jesus, Viviane Silva de (2023)
Socio-environmental problems are being increasingly discussed in schools. In fact, the growth of cities and consumer relations in the capitalist world, that is, consumerism, promote greater generation of impacts in the most diverse types of environments through the solid waste generated. Therefore, it is not uncommon to perceive that the extraction of natural mineral resources for the production of industrialized products present in the daily life of society, intensified the generation of solid waste and the irregular disposal in "dumps", reflecting the need to emphasize debates and problematizations about the use of natural resources interfering with its existence and socio-environmental relations. This theme, when worked at school, contributes to a broader view of students within the environmental field, in the social, health and economic spheres. For this reason, the student must be integrated into such a condition of approach through the use of the active learning resource and the pedagogical strategies that have as one of the basic principles the placement of the student as a center of knowledge, the general objective of the research is to analyze the potentialities developed in students from the use of active learning in dealing with the issue of local solid waste. As specific objectives, we propose to identify the main problems generated by the inadequate disposal of urban solid waste in Simão Dias; evaluate students' prior knowledge about the problem of improper disposal of solid waste in the city; and, preparing a booklet that can contribute to the process of raising awareness about the issue of solid waste. The method used in the research was the HypotheticalDeductive, the research questions are: a) How can active learning contribute to the construction of knowledge about the issue of solid waste by students? b) What are the problems generated by the inadequate disposal of urban solid waste in Simão Dias? the methodology is of an explanatory nature, as it seeks to understand the factors that corroborate the socioenvironmental impacts, bibliography (books, articles, dissertations and theses), carrying out 13 stations that contributed to the construction of the booklet aimed at Basic Education students. The students who participated in the survey were those in the ninth grades A and B who are regularly enrolled and include 55 students from Escola Municipal Cícero Ferreira Guerra. In addition, the experience emphasized the importance of Environmental Education for coherent habits, through pedagogical activities called rotation by stations, bringing gaps in the teaching and learning process as answers to the research, as well as presenting the potentialities developed in students from of the use of active le